1991
DOI: 10.1136/gut.32.6.654
|View full text |Cite
|
Sign up to set email alerts
|

Total orthotopic allogeneic small bowel transplantation in rats: effect of allograft irradiation combined with cyclosporine-A therapy.

Abstract: Rejection and graft versus host disease are prominent features in small bowel allotransplantation in rats. Cyclosporine treatment of the recipient and irradiation of the donor were used to circumvent these phenomena in the WAG to brown Norway rat model. Irradiation ofthe donor with five or 10 Gy did prevent graft versus host disease but resulted in a more vigorous rejection of small bowel aliografts in untreated recipients (mean (SEM) survival times of 11.5 (0.4) (n=8) and 7*5 (0.9) (n=11) days respectively, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(5 reference statements)
2
2
0
Order By: Relevance
“…When our recipients of a graft pretreated with ALS received immunosuppressive treatment with CyA, no adverse effect on graft survival was seen anymore, whereas clinical GVHD remained suppressed. This important finding is in accordance with earlier findings from our laboratory that show that irradiation of the donor with 5 or 10 Gy eliminated clinical GVHD and led to significantly accelerated graft rejection [18]. When recipients of a graft that was irradiated with 5 or 10 Gy received immunosuppressive treatment with CyA, graft survival was prolonged in both groups, whereas clinical GVHD did not occur.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When our recipients of a graft pretreated with ALS received immunosuppressive treatment with CyA, no adverse effect on graft survival was seen anymore, whereas clinical GVHD remained suppressed. This important finding is in accordance with earlier findings from our laboratory that show that irradiation of the donor with 5 or 10 Gy eliminated clinical GVHD and led to significantly accelerated graft rejection [18]. When recipients of a graft that was irradiated with 5 or 10 Gy received immunosuppressive treatment with CyA, graft survival was prolonged in both groups, whereas clinical GVHD did not occur.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that irradiation of the donor with 5 or 10 Gy prevents the occurrence of clinical GVHD and leads to accelerated graft rejection. This study also gave indirect evidence that subclinical GVHD may benefit graft survival [18]. However, most studies on GVHD following small bowel transplantation have used…”
mentioning
confidence: 79%
“…When our recipients of a graft pretreated with ALS received immunosuppressive treatment with CyA, no adverse effect on graft survival was seen any more, whereas clinical GVHD remained suppressed. This important finding is in accordance with earlier findings from our laboratory [115]. The usefulness of manipulating this balance for future clinical SBT remains to be established since it is as yet unclear whether this balance theory is a rat strain-dependent phenomenon and whether GVHD will even be a clinical problem.…”
Section: Graft-versus-host Disease After Small Bowel Transplantationsupporting
confidence: 90%
“…We showed that irradiation of the donor with 10 Gy 1 day before fully allogeneic SBT in the WAG-to-BN rat model completely eliminated GVHD and significantly shortened survival times [114]. Moreover, CyA treatment of the recipient was unable to completely override this effect [115]. Pretreatment of the donor with ALS also eliminated clinical GVHD and led to significantly accelerated rejection [12].…”
Section: Graft-versus-host Disease After Small Bowel Transplantationmentioning
confidence: 99%